Synthesis of levulinic acid-based polyol ester and its influence on tribological behavior as a potential lubricant. Issue 122 (24th November 2015) - Ji, Hairui; Wang, Bingwu; Zhang, Xu; Tan, Tianwei
Abstract : Levulinic acid (LA) was used to prepare lubricant base stocks by esterification with three different polyols including neopentyl glycol (NPG), trimethylolpropane (TMP), and pentaerythritol (PE) in the presence of sulfuric acid. Abstract : Levulinic acid (LA) has been identified by the US Department of Energy as a top platform chemical and regarded as one of the twelve most promising molecules derived from biomass. In this study, it was used to prepare lubricant base stocks by esterification with three different polyols including neopentyl glycol (NPG), trimethylolpropane (TMP), and pentaerythritol (PE) in the presence of sulfuric acid. The crude product was distilled to obtain the target product with a purity above 95%. The products of the polyol ester were characterized using 1 H NMR and mass spectrometry techniques. The lubricant properties, such as kinematic viscosity, viscosity index, and pour and flash points, were evaluated using standard ASTM methods. Among the base stocks prepared, TMP-tri-LA ester exhibited superior lubricant properties like good kinematic viscosity at 40 °C (87.28) and at 100 °C (8.42), a viscosity index of 48, a low pour point (−25 °C), a high flash point (238 °C), a low cloud point (−4 °C), a low copper strip corrosion class (1a), and low volatility at 120 °C (0.41%). Wear prevention characteristics of this ester were tested and produced a low coefficient of friction and small wear scar diameters. It was found that this kind of polyol ester is suitable for lubricant base stocks.